2009
DOI: 10.1016/j.ijpe.2009.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Container shipping on the Northern Sea Route

Abstract: International audienceSince the beginning of the 20th century, the principal commercial maritime routes have changed very little. With global warming, the Northern Sea Route (NSR) has opened up as a possible avenue of trade in containerized products between Asia and Europe. This paper verifies the technical and economic feasibility of regular container transport along the NSR. By adopting a model schedule between Shanghai and Hamburg, we are able to analyze the relative costs of various axes in the Asia–Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
128
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(137 citation statements)
references
References 21 publications
1
128
0
Order By: Relevance
“…Commercial NWP transits between Japan, and Eastern Canada are estimated to be financially viable, although how much is debated (Somanathan et al, 2009). Commercial NEP transits between Shanghai and Hamburg are currently viable, yet double the cost of the traditional route (Verny and Grigentin, 2009).…”
Section: Diversion Through Arctic Future Year Scenariosmentioning
confidence: 99%
“…Commercial NWP transits between Japan, and Eastern Canada are estimated to be financially viable, although how much is debated (Somanathan et al, 2009). Commercial NEP transits between Shanghai and Hamburg are currently viable, yet double the cost of the traditional route (Verny and Grigentin, 2009).…”
Section: Diversion Through Arctic Future Year Scenariosmentioning
confidence: 99%
“…Comparing this result to data provided by VERNY and GRIGENTIN (2009) related to their study concerning container shipping on the Northern Sea route versus the Trans-Siberian Railway and the Suez Canal route, they found that the railway route is 30% more expensive. Consequently, the transfer of one container from Eilat to Ashdod through the Red-Med railway could be 78,5USD x 1.3 = 102USD.…”
Section: The Train Transportation Costmentioning
confidence: 49%
“…Similarly, an overland rail route exists across Asia, mainly using the Trans-Siberian, linking Asian regions with Europe (Verny and Grigentin 2009;Lasserre and Huang 2015).…”
Section: Sea Shipping In Thementioning
confidence: 99%